KESETARAAN GENDER DALAM POLITIK - AlRafni AlRafni (Universitas Islam Negeri Imam Bonjol Padang, 2013)
Political parties have a strategic role in increasing women's representation in the legislature. The patterns and system development of gender responsive female cadres can be entry points for strengthening the capacity of regional legislatures. The articles taken from some of the results of the studies recommend the need for coaching affirmative treatment of women cadres from both the structure of the party or outside the party structure. Similarly, in terms of internal party strategy or policy, materials, and methods of coaching.Keywords : Political parties, development of female cadres, strengthening the capacity of local legislativeCopyright © 2013 by Kafa`ah All right reservedDOI : 10.15548/jk.v3i2.44